THE USE OF TRADITIONAL DHSP BALI YOGA AND MEDITATION PRACTICES ON REDUCING BLOOD GLUCOSE LEVELS - Setiabudi, Agung; Agastya Punia, I Gede Eka Agung; Setiani, Putu; Puspita, Lussy Ayu; Manggala, Kadek Satya (Syntax Corporation Indonesia, 2025)
The practice of yoga and meditation at Dharma Hidup Singin Prana Bali has a deep meaning in maintaining physical and mental balance, as well as supporting mental health in the midst of the dynamics of modern life. Yoga has been shown to be effective in helping to manage blood sugar levels through meditation and yoga practices. This study uses quantitative research methods, specifically using a quasi-experimental design with pre-test and post-test, to assess the results before and after the intervention for the purpose of evaluating blood sugar levels from the results of yoga and meditation exercises. Descriptive analysis of 32 samples showed that the mean glucose values after the intervention showed a decrease. Statistical analysis of Kolmogorov-Smirnov pre-test with P = 0.183 data showed normal and homogeneous distribution. The test of the difference in the results of the pre-test and post-test research using the Paired sample T-test analysis with 95% confidence showed significance = 0.000 Because the significance result of 0.000 which means < 0.001 where 0.001<0.05 so that there is a statistically significant difference. Traditional Dhsp Bali yoga and meditation exercises involving breathing exercises, postures and Yoga have been shown to be effective against the balance and decrease of glucose levels in the blood.